Su alcune riconiazioni di stateri tarantini dal commercio numismatico - Marrazzo , Vincenzo (KOINON: The International Journal of Classical Numismatic Studies, 2024)
This study focuses on four Taranto staters of groups 3 and 4 Fischer-Bossert (c. 490-470 BC) from auction catalogues and overstruck on coins from Corinth and, as yet unpublished, from Gela. The numismatic analysis of the specimens reveals some clues which, together with the intrinsic elements of coinage, the circulation data, and the comparison with other Magna Graecia issues, allow us to clarify the chronology proposed by Fischer-Bossert for these issues.